Analysis of the gut bacterial community of wild larvae of Anastrepha fraterculus sp. 1: effect of host fruit, environment, and prominent stable associations of the genera Wolbachia, Tatumella, and Enterobacter - Salgueiro, Julieta; Nussenbaum, Ana Laura; Milla, Fabian Horacio; Asimakis, Elias D.; Goane, Lucía; Ruiz, María Josefina; Bachmann, Guillermo Enrique; Vera, María Teresa; Stathopoulou, Panagiota; Bourtzis, Kostas; Deutscher, Ania T.; Lanzavecchia, Silvia Beatriz; et al. (Frontiers Media, 2022)
The genus Anastrepha (Diptera Tephritidae) includes some of the most important fruit fly pests in the Americas. Here, we studied the gut bacterial community of 3rd instar larvae of Anastrepha fraterculus sp. 1 through Next Generation Sequencing (lllumina) of the V3-V4 hypervariable region within the 16S rRNA gene. Gut bacterial communities were compared between host species (guava and peach), and geographical origins (Concordia and Horco Molle in Argentina) representing distinct ecological scenarios. In addition, we explored the effect of spatial scale by comparing the samples collected from different trees within each geographic origin and host species. We also addressed the effect of fruit size on bacterial diversity. The gut bacterial community was affected both by host species and geographic origin. At smaller spatial scales, the gut bacterial profile differed among trees of the same species and location at least in one host-location combination. There was no effect of fruit size on the larval gut bacteriome. Operational Taxonomic Units (OTUs) assigned to Wolbachia, Tatumella and Enterobacter were identified in all samples examined, which suggest potential, non transient symbioses. Better knowledge on the larval gut bacteriome contributes valuable information to develop sustainable control strategies against A. fraterculus targeting key symbionts as the Achilles’ heel to control this important fruit fly pest.